Correlation between Interleukin-1, Interleukin-6 with RANKL/OPG Ratio on Bone Remodelling in SLE Patient - Najirman Najirman (Indonesian Rheumatology Associantion, 2026)
Background: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease characterized by the presence of pathogenicautoantibodies that attack many organ systems, giving rise to various clinical manifestations. Osteoporosis is one of the complications of SLE. Interleukin 1 and Interleukin 6, which are the main inflammatory cytokines in SLE, are associated with the Receptor Activator of Nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) ratio, which are indicators of bone loss. This study aims to analyze the relationship between serum IL1 and IL 6 with RANKL/OPG ratio in LES.(1,2,3) Methods: This was an analytical observational study with a cross-sectional design involving 30 patients with SLE. Serum IL-1, IL-6 and RANKL/OPG rasio levels were measured using ELISA. Results: There is a strong correlation between IL-1 and RANKL/OPG ratio (r=0.771) withp value <0.001 and weak degree of correlation between IL-6 and RANKL/OPG ratio (r=0.37) with p value 0.022. Conclusions:increased levels of IL1 and IL 6 followed by an increase in the RANKL/OPG ratio